Kajian penentuan sebatian organoarsenik menggunakan pelbagai kaedah voltammetri dengan elektrod titisan raksa tergantung - Marpongahtun, Marpongahtun (2005)
Various voltammetric methods including cyclic voltammetry (CV), differential pulse cathodic stripping voltammmetry (DPCSV), differential pulse anodic stripping voltammmetry (DPASV) and differential pulse voltammmetry (DPV) were used for the determination of six organoarsenic compounds, namely (phenylarsonic acid (PAA), para-arsanilic acid (p-ASA), ortho-arsanilic acid (o-ASA), 4-nitrophenylarsonic acid (4-NPAA, nitarsone), 3-nitro-4-hydroxy phenylarsonic acid (3-NHPAA, roxarsone) and para-ureidophenylarsonic acid (p-UPAA, carbarsone). Hanging mercury drop electrode (HMDE) was used as the working electrode. Dilute 0.1 M HCl and Britton Robinson (BR) buffer 0.04 M at pH = 3.0 were used as the supporting electrolyte solutions. The experimental parameters optimized are the effects of scan rate, pH, initial potential, accumulation potential, accumulation time and interferences. DPCSV method was used for indirect determination of p-ASA and o-ASA based on diazotization and coupling reaction. Cyclic voltammogram cathodic scan showed an irreversible peak of arsonic acid group for PAA, p-ASA, o-ASA and p-UPAA. Whereas two irreversible peaks of nitro and acid arsonic groups were observed for 4-NPAA and 3-NHPAA. Anodic scan for all of the compounds showed two oxidation peaks for phenylarsine and phenylarsenous oxide groups respectively. Two couples of redoxs peaks for phenylarsine and phenylarsenous oxide groups were identified after two-cycles of cyclic voltammogram. By utilizing a pre-scan process, the DPCSV method showed two sharp peaks of phenylarsenous oxide and phenylarsine groups respectively for PAA, p-ASA, o-ASA, p-UPAA. On the other hand, one broad and low reduction peak was observed for acid arsonic group. DPCSV method also showed reduction peak of nitro group for organoarsenic compounds that certain nitro groups namely the 4-NPAA and 3-NHPAA. DPV cathodic scan result for PAA, p-ASA, o-ASA, p-UPAA showed one reduction peak of acid arsonic group, while two reduction peaks of nitro and acid arsonic group for 4-NPAA. The DPASV analysis for all the compounds, showed two oxidation peaks of phenyl arsine and phenylarsenous oxide. The method was validated by using reproducibility, limit of detection and recovery study. The limit of detection for all organoarsenic compounds were found to be in the range of 1.48 to 4.56 x 10-8 M (DPCSV), 1.35 to 4.27 x 10-8 M (DPASV) and 2.3 x 10-8 M (DPV cathodic scan). The RSD were found to be in range of 1.35 % - 4.64 %, while the percentage of recovery studies in the range of 80 % - 98.67 %. DPCSV method was succesfull to differentiate p-ASA and o-ASA via diazotization and coupling reaction at various conditions.